Pricing, distribution and adoption of genetically modified seeds under alternative information regimes - Arnab K. Basu; Matin Qaim (University of Bonn, Center for Development Research (ZEF), 2007)
This paper considers genetically modified (GM) seed adoption decisions by farmers in a developing country under two alternative information regimes (with and without perfect information regarding production conditions) that allows the monopolist producer of GM seeds to either practice perfect discrimination or uniform pricing. Under each regime we analyze two scenarios: when the government can and cannot credibly commit to the announced form of welfare enhancing intervention in the domestic seed market. We show that the optimal policy under either information regime is to subsidize the price of conventional seeds. The optimal size of the conventional seed subsidy depends systematically, in turn, on the (i) marginal cost of GM and conventional seeds, (ii) price of chemical pesticides, (iii) degree to which GM seeds increase productivity, (iv) range of pest pressure among farmers, and (v) intensity of seed usage (GM and conventional). Nonetheless, our findings pinpoint time-inconsistency of government policies as a possible reason for sub-optimal coverage of GM seeds in developing countries. – – Diese Arbeit untersucht Entscheidungsstrategien von Bauern hinsichtlich der Anwendung genetisch veränderten Saatguts (genetically modified, GM) in zwei Entwicklungsländern mit unterschiedlichen Informationssystemen (mit und ohne Informationen über die Produktionsbedingungen), die es dem Monopolisten-Erzeuger von GM Saatgut erlauben, entweder perfekte Diskriminierung zu praktizieren oder einheitliche Preissysteme zu etablieren. Innerhalb jedes Informationssystems analysieren wir zwei Szenarien: Ob die Regierung in der Lage ist oder nicht, sich glaubwürdig zu der angekündigten, wohlfahrtssteigernden Form der Intervention auf dem heimischen Saatgutmarkt zu verpflichten. Wir zeigen, dass die optimale Verfahrensweise in jedem Informationssystem eine Subvention des Preises konventioneller Samen ist. Die ideale Höhe der konventionellen Saatgutsubvention hängt systematisch davon ab, (i) wie hoch die Grenzkosten der GM und des konventionellen Saatguts sind, (ii) wie hoch die Kosten für die chemischen Pestizide sind, (iii) in welchem Maß GM die Produktivität erhöhen, (iv) wie sehr die Pflanzungen von Schädlingen befallen werden und (i) wie hoch die Intensität des Saatgutgebrauchs ist (GM und konventionell). Trotzdem zeigen unsere Untersuchungen genau auf, dass die zeitliche Unbeständigkeit der jeweiligen Regierungsstrategie ein Grund für die sub-optimale Verbreitung der GM Samen in Entwicklungsländern sein können.
Keywords: 330